Colonization of root cells and plant growth promotion by Piriformospora indica occurs independently of plant common symbiosis genes - Banhara, Aline; Ding, Yi; Kühner, Regina; Zuccaro, Alga; Parniske, Martin (Frontiers in Plant Science, 2015)
Arbuscular mycorrhiza (AM) fungi (Glomeromycota) form symbiosis with and deliver nutrients via the roots of most angiosperms. AM fungal hyphae are taken up by living root epidermal cells, a program which relies on a set of plant common symbiosis genes (CSGs). Plant root epidermal cells are also infected by the plant growth-promoting fungus Piriformospora indica (Basidiomycota), raising the question whether this interaction relies on the AM-related CSGs. Here we show that intracellular colonization of root cells and intracellular sporulation by P. indica occurred in CSG mutants of the legume Lotus japonicus and in Arabidopsis thaliana, which belongs to the Brassicaceae, a family that has lost the ability to form AM as well as a core set of CSGs. A. thaliana mutants of homologs of CSGs (HCSGs) interacted with P. indica similar to the wild-type, suggesting that AM fungi and P. indica exploit different host pathways for infection. Moreover, increased biomass of A. thaliana evoked by P. indica was unaltered in HCSG mutants. We conclude that colonization and growth promotion by P. indica are independent of the CSGs.